2021
DOI: 10.1007/s10620-021-06872-z
|View full text |Cite
|
Sign up to set email alerts
|

Does Famotidine Reduce the Risk of Progression to Severe Disease, Death, and Intubation for COVID-19 Patients? A Systemic Review and Meta-Analysis

Abstract: Background Famotidine was reported to potentially provide benefits to Coronavirus Disease 2019 (COVID-19) patients. However, it remains controversial whether it is effective in treating COVID-19. Aims This study aimed to explore whether famotidine use is associated with reduced risk of the severity, death, and intubation for COVID-19 patients. Methods This study was registered on International Prospective Register of Systematic Reviews (PROSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 48 publications
(47 reference statements)
0
24
0
Order By: Relevance
“…In the second category of reports which were less enthusiastic about famotidine, some did suggest against the usage of famotidine ( Cheung et al, 2020 ; Yeramaneni et al, 2021 ; Zhou et al, 2020 ), while others found no association for famotidine or PPIs and COVID-19 therapeutic value ( Elmunzer et al (2020) and Fan et al (2021) ). • Era 2 : Meta-analyses of the primary literature reports : Three such analyses have appeared thus far, with again varying results: Sethia et al (2020b) were cautiously pro-famotidine, while Sun et al (2021) and Kamal et al (2021) were more neutral/negative, determining for the most part that no association (positive or negative) was statistically justifiable. Why the inconsistency in whether or not famotidine is indicated for COVID-19, even at the level of a meta-analysis?…”
Section: Has Our Understanding Progressed?mentioning
confidence: 99%
See 1 more Smart Citation
“…In the second category of reports which were less enthusiastic about famotidine, some did suggest against the usage of famotidine ( Cheung et al, 2020 ; Yeramaneni et al, 2021 ; Zhou et al, 2020 ), while others found no association for famotidine or PPIs and COVID-19 therapeutic value ( Elmunzer et al (2020) and Fan et al (2021) ). • Era 2 : Meta-analyses of the primary literature reports : Three such analyses have appeared thus far, with again varying results: Sethia et al (2020b) were cautiously pro-famotidine, while Sun et al (2021) and Kamal et al (2021) were more neutral/negative, determining for the most part that no association (positive or negative) was statistically justifiable. Why the inconsistency in whether or not famotidine is indicated for COVID-19, even at the level of a meta-analysis?…”
Section: Has Our Understanding Progressed?mentioning
confidence: 99%
“…[Note that CIDO is one of many biomedical ontologies gathered at BioPortal ( Whetzel et al, 2011 ).] A potential source of confusion in the recent famotidine literature, taken in totality, is that recent meta-analyses ( Sethia et al, 2020b ; Kamal et al, 2021 ; Sun et al, 2021 ) of retrospective, observational, cohort-based studies have not always enforced a clean delineation between the two MOAs mentioned above (i.e., PPI, H2RA), at least when drawing their conclusions. As a case in point, some primary studies have found that famotidine is beneficial whereas PPIs offered “no protective effect” ( Freedberg et al, 2020a ); another study found no positive effect of famotidine and also no deleterious effect of PPIs ( Elmunzer et al, 2020 ); another found no association between PPIs and a different H2RA (ranitidine), in terms of likelihoods of both COVID-19 infection and death ( Fan et al, 2021 ); a pair of studies found no evidence for additional risks or benefits, for neither famotidine nor PPIs ( Cheung et al, 2020 ; Shoaibi et al, 2021 ); and, finally, another recent study ( Zhou et al, 2020 ) found greater risks of association with morbidity or severe illness for famotidine and PPIs (each one, individually).…”
Section: Introduction: Possible Systematic Approaches?mentioning
confidence: 99%
“…Our current analysis is different from the two meta-analyses published by Kamal et al and Sun et al for four main reasons: 1) to reduce discrepancies in patient characteristics, we did not include the studies by Cheung et al and Zhou et al as they included all patients with COVID-19 in Hong Kong, including outpatient, inpatient, and emergency settings as opposed to four other studies where only hospitalized patients were included (19,20); 2) moreover, since both studies drew from the same centralized Hong Kong database, some patients would be counted twice within the same time period if both were included in a meta-analysis as in Kamal et el (19); 3) additionally, we chose not to meta-analyze the results of studies that presented a composite endpoint with the results of studies that presented only an endpoint of mortality since they represent different degrees of severity (19,20); 4) finally, we did not meta-analyze OR along with HR reported by different -10 -studies since the rare event assumption is not met (20). In fact, across four studies, the incidence of the composite outcome ranged from 21% to 37% (14-17).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, two meta-analyses on the use of famotidine in patients with COVID-19 have been published (19,20). However, these meta-analyses may have introduced heterogeneity in patient population due to the inclusion of studies with non-hospitalized patients diagnosed with COVID-19 (13,18).…”
Section: Introductionmentioning
confidence: 99%
“…This combination of repurposed drugs is based on the labeled MOA of famotidine and celecoxib as antiin ammatory agents. To distinguish from suboptimal treatment protocols which typically employ inadequate doses of famotidine (Malone, 2021;Shoaibi et al, 2021;Sun et al, 2021), this binary drug combination is referred to as High Dose (HD) famotidine + celecoxib or famcox.…”
Section: Discussionmentioning
confidence: 99%